Analysis of the Influence of Structural Profile Differences Between Tambak Lorok Traditional Fishing Vessels and BKI Standard Criteria - Hartono Yudo; Wilma Amiruddin; Alfiy Alfatarizqi (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
Traditional fishing vessels in Tambak Lorok are commonly constructed based on inherited craftsmanship and empirical experience, without adherence to any formal classification standard. Consequently, variations in the mechanical strength of wooden materials due to dimensional differences require further investigation. This study aims to examine the differences in destructive stress values that occur after the vessel experiences an impact, with reference to the Bureau of Classification Indonesia (BKI) criteria. The methodology involves recalculating the structural dimensions of wooden ship components following BKI standards and conducting localised impact tests at a standard berthing velocity of 0.25 m/s, with vessel speeds ranging from 1 knot to 2.5 knots. The analytical and experimental findings reveal a construction weight reduction of 258 kg, equivalent to approximately 42% lighter than the conventional design. The safe stress limits were determined to be 102.88 MPa on the frame and around 30 MPa on the hull plating under a 2-knot collision. These results demonstrate that applying BKI criteria enhances both structural efficiency and economic value while maintaining safety under standard berthing conditions.